2013
DOI: 10.1016/j.vacuum.2013.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Ti3SiC2-formation during Ti–C–Si multilayer deposition by magnetron sputtering at 650 °C

Abstract: Titanium Silicon Carbide films were deposited from three separate magnetrons with elemental targets onto Si wafer substrates. The substrate was moved in a circular motion such that the substrate faces each magnetron in turn and only one atomic species (Ti, Si or C) is deposited at a time. This allows layer-by-layer film deposition. Material average composition was determined to Ti0.47Si0.14C0.39 by energy-dispersive X-ray spectroscopy. High-resolution transmission electron microscopy and Raman spectroscopy wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…It is worth noting that Ti 5 Si 3 was identified as a transient phase only existing in a narrow range of temperatures from 412 to 434 • C [18]. In another work, Vishnyakov et al identified Ti 5 Si 3 (C x ) with dissolved carbon in Ti-Si-C multilayers deposited by magnetron sputtering at 650 • C [35]. The first mechanism, which consists of the formation an amorphous layer at the Ti-Si interface before Ti silicides crystallize, cannot be ruled out.…”
Section: Formation Of Tisi and C 49 Tisimentioning
confidence: 99%
“…It is worth noting that Ti 5 Si 3 was identified as a transient phase only existing in a narrow range of temperatures from 412 to 434 • C [18]. In another work, Vishnyakov et al identified Ti 5 Si 3 (C x ) with dissolved carbon in Ti-Si-C multilayers deposited by magnetron sputtering at 650 • C [35]. The first mechanism, which consists of the formation an amorphous layer at the Ti-Si interface before Ti silicides crystallize, cannot be ruled out.…”
Section: Formation Of Tisi and C 49 Tisimentioning
confidence: 99%
“…Ternary compounds, such as Cr2AlC [1], Ti3SiC2 [2][3][4], and Ti3AlC2 [5,6], have attracted considerable interest, primarily because of their unique properties combining many merits of both metals and ceramics. Like metals, they show high thermal and electrical conductivity, and are easy to machine, resistant to thermal shock, and tolerant to damage.…”
Section: Introductionmentioning
confidence: 99%
“…This phase can accommodate considerable amounts of C and thus is usually referred to as 69 Ti 5 Si 3 C x . 23,24 It has hexagonal crystal structure with P6 3 /mcm space group in which C atoms sit at 2b 70 positions. For the sake of brevity, we will write Ti 5 Si 3 here.…”
mentioning
confidence: 99%